Analisis Dampak Media Sosial terhadap Literasi Politik dan Partisipasi Demokratis Generasi Z di Era Post-Truth: Analisis Dampak Media Sosial terhadap Literasi Politik dan Partisipasi Demokratis Generasi Z di Era Post-Truth - Supri Yanto; Irmala Sari, Putri (Civic Education Perspective Journal, 2025)
This research examines digital transformation in political education with a focus on the impact of social media on political literacy and democratic participation of Generation Z in the post-truth era. The post-truth phenomenon characterized by the easy spread of disinformation through social media has created new challenges in political education. The study used a mixed method approach involving 450 students aged 18-24 years from five public universities in Indonesia. Data were collected through online surveys, focus group discussions, in-depth interviews with political education experts, and social media content analysis. The results showed that 78% of respondents relied on social media as the main source of political information, but only 35% had sufficient ability to verify the truth of the information. The study found a significant correlation between the intensity of social media use and the level of political literacy (r=0.67, p<0.01) and the level of democratic participation (r=0.58, p<0.01). Based on these findings, the research proposes a digital political education model that integrates the digital citizenship approach with conventional political education. The model emphasizes the development of information verification skills, critical thinking, and responsible democratic participation in the digital space. The results contribute to the development of political education strategies that are adaptive to digital transformation.